Formulasi Dan Evaluasi Sifat Fisik Blush On Powder Ekstrak Buah Tomat (Solanum lycopersicum L.) Sebagai Pewarna Alami - Eryani, Mikhania Christiningtyas; Syuhuriah, Ainin; Azizah, Siti Nur; Husni, Patihul (Faculty of Pharmacy, University of Jember, 2025)
Blush on is a cosmetic product that is used to provide color or add aesthetics to facial makeup. Tomato fruit (Solanum lycopersicum L.) contains red carotenoid pigments which can be used as natural dyes. This research aims to formulate and evaluate the physical properties of blush on tomato fruit extract with concentrations of 3% (F1),5% (F2) and 7% (F3). The results of organoleptic research showed that F1 was light orange, F2 was bright orange and F3 was bright orange. The entire formula smells of rosae, has a smooth and homogeneous texture. The pH value of the entire formula is 6.0. Evaluation of spreadability shows that the entire formula adheres after 5 applications. The conclusion of this research is that tomato fruit extract has an effect on the physical properties of blush on powder, namely organoleptic odor and color. However, it has no effect on organoleptic texture, pH, homogeneity and spreadability